Developing a Public Health Risk Assessment Toolkit for Mass Gatherings and Trialling for an International Multi-Sport Mass Gathering Event. Issue Volume 34:Issue s1(2019) (May 2019) - Bloomer, Ellen; Endericks, Tina
Abstract : Introduction: Risk assessment for mass gatherings (MGs) is undertaken to enable public health authorities to systematically identify and assess the generic characteristics of an MG, which introduce or enhance particular threats and develop measures to reduce or mitigate these threats. The World Health Organization Collaborating Centres on Mass Gatherings and Global Health Security (WHO CCs) produced a comprehensive guide to MGs called "Public Health for Mass Gatherings: Key Considerations" (KC2). This is being converted into an eLearning resource. A public health risk assessment toolkit is being developed by the WHO CCs to complement and guide organizers in their planning process for the health risks associated with an MG event. Preparations for the Birmingham 2022 Commonwealth Games (BCG) are underway and it is important to involve a public health element in the planning for the BCG. Aim: To develop a public health risk assessment toolkit for MGs and pilot it as part of the planning process for the BCG. Methods: Based on KC2 principles, methods included developing and finalizing a public health risk assessment toolkit for MGs. This study also piloted the toolkit for the BCG. Results: A toolkit will be developed. Key learning will be documented on how the toolkit can be improved. The pilot will identify the key public health risks for the BCG, and assess how to mitigate them. Discussion: The development of this toolkit will be an innovative contribution to the resources available for those organizing MGs. It will support organizers to conduct risk assessments and thus maximize the potential for health from the event. Piloting the toolkit for the BCG is an opportunity for validating it, and provides valuable learning for its use in future events. It will support the risk assessment process for the BCG and share learning regarding the key risks for this event.